Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s00455-020-10238-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Chin Tuck on Laryngeal Penetration: Quantitative Assessment

Abstract: The effectiveness of the chin tuck maneuver is still controversial, despite being widely used in clinical practice. The chin tuck maneuver has been shown to be able to reduce or eliminate aspiration in a group of patients with a number of favorable conditions, but its effectiveness in preventing or managing penetration remains unclear. This study was designed to investigate whether the chin tuck maneuver is effective in reducing penetration. Images from a videofluoroscopic swallowing study (VFSS) taken from 76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…To treat or improve symptoms of dysphagia, various methods have been reported. Conventional treatment methods such as oropharyngeal exercises and compensated maneuvers, such as the chin-tuck maneuver, are widely used to improve the symptoms of dysphagia [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…To treat or improve symptoms of dysphagia, various methods have been reported. Conventional treatment methods such as oropharyngeal exercises and compensated maneuvers, such as the chin-tuck maneuver, are widely used to improve the symptoms of dysphagia [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The chin-tuck maneuver, also known as the chin-down posture ( Figure 4 ), is a commonly used compensatory strategy; however, its reported effectiveness in studies in patients with PD with dysphagia has varied ( Ra et al, 2014 ; Saconato et al, 2016 ). These early studies often lacked clear objective markers, however, more recent evidence from studies using objective outcomes has demonstrated that it has a significant benefit in reducing laryngeal penetration in patients with PD with dysphagia ( Ko et al, 2021 ). However, in real-world clinical practice, while the chin-tuck maneuver has proven benefits and is relatively easy to explain, for patients with PD who may have existing postural problems or tremors, it may be challenging initially ( Schindler et al, 2021 ).…”
Section: Dysphagia In Parkinson’s Diseasementioning
confidence: 99%
“…The results showed that in the chin-down position, penetration and aspiration were minimized by expanding the epiglottic vallecula and narrowing the laryngeal inlet. In addition, using VFSS, Ko et al 24 investigated the effects of the chin-tuck position on penetration and aspiration in patients with swallowing disorders, as well as factors affecting chin tuck effectiveness; they found that the chin-tuck position reduces the depth and rate of aspiration and also reduces the amount of pharyngeal residues.…”
Section: Efficiency and Stability Of Swallowingmentioning
confidence: 99%
“…However, as the terms defining the chin-tuck position and the reference points for measuring the angles used in the three papers were different, it is difficult to confirm whether these results actually indicate consistency. In addition, Ko et al24 revealed that the chin-tuck maneuver was effective but noted the limitation that neck flexion angles could not be accurately measured, resulting in biased results. This is demonstrated in continuing study by Chin-tuck, in which the neck angles are not accurately measured, and other studies have confirmed that definitions of the chin-tuck position vary JKDS Vol.…”
mentioning
confidence: 99%